Clinical Outcomes of Circumcisions and Prevalence of Complications of Male Circumcisions: A One-Year Retrospective Study in Khyber Teaching Hospital Peshawar - Hazratullah, Amir Taimur Khan, Hamza Khan Shahbazi, Syed Muhammad Haider, Moath Ahmad Abdullah Almuradi, Muhammad Aness Iqbal (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Circumcision of males is a procedure that is frequently performed and has some medical advantages, like decreasing the chances of HIV infection. While common, its consequences may vary from mild to severe. This study seeks to evaluate clinical results and complications of male circumcisions conducted at Khyber Teaching Hospital Peshawar. Methodology: This is a retrospective descriptive and analytic study performed over one year from July 2022 to July 2023. A structured extraction sheet was designed to collect demographic data along with clinical details and outcomes of 186 circumcision cases, which were later analyzed. Results: In the set of 186 cases of circumcision, the cases that experienced complications was 23 (12.37%). The most prevalent complications were observed for incomplete circumcision (43.48%), post circumcision hemorrhage (PCMH) (21.74%), urethrocutaneous fistula / wrong circumcision of congenital hypospadias (13.04%). There was a strong association with the complication rates and the circumcision provider (p<0.001). Doctors had the fewest complications (4.3%), while nurses (39.1%) and traditional circumcisers (34.8%) had higher rates. Circumcision and revision surgery was the most frequent said procedure (31.82%) for first attempt salvage surgeries. Conclusion: The complications that arise from circumcision procedural tasks are profoundly related to the skills of the provider. Outcomes of salvage surgery for circumcision accidents were found to be unsatisfactory in about 30% of the cases, indicating that it is better to avoid these issues rather than trying to remedy them. There is an imperative need for training interventions, protocols, and health promotions to enhance complication outcomes and decrease their occurrence. Keywords: Male circumcision, complications, urethrocutaneous fistula, hypospadias, surgical outcomes, traditional circumcisers.